Incidence of second metachronous head and neck cancers: Population‐based outcomes over 25 years. (30th May 2014) - Tiwana, Manpreet S.; Hay, John; Wu, Jonn; Wong, Frances; Cheung, Winson; Olson, Robert A.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The primary objective was to determine the incidence of second metachronous head and neck cancers (HNC) following an index HNC and estimate their overall survival. Study Design Retrospective cohort study. Methods A total of 1, 658 consecutive primary HNC patients diagnosed in 1986 to 1990 were identified through the prospectively maintained provincial BC Cancer Registry database. They were followed up for a period of 25 years. Survival analysis and second cancer estimates were performed with standard Kaplan‐Meier & Cox regression analysis. Results Out of a total of 443 (27%) second cancers, 89 (5%) second HNC occurred in 1, 658 HNC patients, with an actuarial metachronous HNC incidence rate at 5, 10, 15, 20, and 25 years that was 3.9%, 8.1%, 10.4%, 13.2%, and 14.5%, respectively. Second primary cancer (SPC) in lung and esophagus occurred in 155 (9%) and 32 (2%) patients, respectively. The median follow‐up time for all patients and alive patients was 4.05 years (range, 0.2–25.0 years) and 23.2 years (range, 20.76–25.0 years), respectively. Of second HNC, 83 (93%) were metachronous. Oral cavity (P < 0.001) and oropharyngeal (P < 0.002) index cancers were more likely to develop a metachronous HNC. The overall survival rate for the metachronous HNC patients at 5 years is 15%. SPCs in esophagus and lung had lower overall survival compared to second HNC (P < 0.001). Conclusion Oral cavity and oropharyngeal cancers carry the highest risk of a subsequent metachronous HNC. Given the incidence and prognosis of second HNC, future research should address the frequency and duration of screening the head and neck region for a second cancer. Level of Evidence 2b. Laryngoscope 124:2287–2291, 2014